Development and Pilot Testing of a Cognitive-Behavioral Therapy Digital Service for Body Dysmorphic Disorder. Issue 1 (January 2020) - Wilhelm, Sabine; Weingarden, Hilary; Greenberg, Jennifer L.; McCoy, Thomas H.; Ladis, Ilana; Summers, Berta J.; Matic, Aleksandar; Harrison, Oliver
Abstract: Body dysmorphic disorder (BDD) has a severe presentation and chronic course when untreated. Although effective BDD treatments exist, most individuals do not have access to them. We therefore developed and pilot tested the first smartphone-delivered individual cognitive-behavioral therapy (CBT) treatment for adults with BDD. The digital service was developed via user-centered design, integrating input from engineering, design, and psychology experts, plus BDD patient consultants. We conducted a 12-week open pilot trial ( N = 10) to describe preliminary results for feasibility, acceptability, and treatment outcome. Attrition rates (0%) and feedback on usability and satisfaction indicated that smartphone-based CBT for BDD may be feasible, acceptable, and satisfactory. Initial results suggest that smartphone-based CBT for BDD may hold promise for improving BDD symptom severity, BDD-related insight, functional impairment, and quality of life, as scores from baseline to posttreatment improved with large-to-very large effects; depression improved with a medium effect. Ninety percent of participants were responders at posttreatment and 3-month follow-up. Smartphone-based CBT for BDD may have strong potential as a standardized, low cost, and accessible treatment for this debilitating illness. A test of efficacy is merited as a next step, using a well-powered, randomized control trial design. Highlights: Developed and pilot tested the first smartphone-delivered CBT service for BDD A 12-week open trial suggests the app may be feasible, acceptable, and satisfactory Severity and impairment reduced with large effects Insight and quality of life improved with large effects Smartphone-based CBT for BDD shows promise as a low-burden intervention